Discovery of a Chinese familial deletion 18p syndrome due to a false positive result on noninvasive prenatal testing. Issue 2 (16th November 2020) - Ju, Duan; Zuo, Zhigang; Li, Xiaozhou; Shi, Yunfang; Zhang, Ying; Xue, Fengxia
Abstract: Clinical manifestations of deletion 18p syndrome vary a lot, which makes it easily overlooked in the clinical practice. Familial transmission of deletion 18p syndrome is rare. We report a Chinese familial deletion 18p syndrome, which was diagnosed by anatomizing the underlying reason for the discrepancy between noninvasive prenatal testing (NIPT) and prenatal diagnosis. A 35‐year‐old pregnant woman was recruited to our center owing to the abnormal NIPT result with a high risk of chromosome 18 monosomy. However, the karyotype of the fetus was normal after amniocentesis. Further analysis indicated that the pregnant woman herself had an abnormal karyotype of 46, XX, del(18)(p11.2), (arr18p11.32p11.21[136, 227‐15, 099, 116]×1) and her first 12‐year‐old son had got the same deletion of 18p as her. A distinct phenotype variability was noted although they share identical deletion. We consider that adequate clinical genetic counseling is vital for women with adverse pregnancy history before getting pregnant. Maternal CNVs may be one of the main causes of the false‐positive result on NIPT. NIPT, especially extended NIPT may provide extra valuable evidence when used as routine prenatal screening method.